(Invited)Recent Progress in the Understanding of the Electrocatalysis of the CO-Tolerant Hydrogen Oxidation Reaction in Polymer Electrolyte Fuel Cells. (26th March 2018) - Tryk, Donald A.; Shi, Guoyu; Yano, Hiroshi; Inukai, Junji; Uchida, Hiroyuki; Iiyama, Akihiro; Matsumoto, Masashi; Tanida, Hajime; Arao, Masazumi; Imai, Hideto
Abstract : Recent combined experimental and theoretical efforts have led to progress in the understanding of hydrogen oxidation and oxygen reduction reactions in fuel cells. The hydrogen anode in the polymer electrolyte fuel cell needs to be tolerant of CO concentrations in the tens of ppm in the reformed natural gas fuel. We have found that various Pt-M (M = Fe, Co, Ni, Ru) nanoparticulate alloys have significantly greater tolerance than pure Pt, and also, the area-specific hydrogen oxidation activity is higher. We have been able to explain the CO tolerance and catalytic activity with a novel metal-to-metal hydrogen spillover mechanism that is based on density functional theory calculations. The latter have also been supported by in situ spectroscopic measurements, both X-ray absorption and infrared reflection-absorption.